EVALUACIÓN DE TENSIONES RESID.UALES EN DISCOS COMPACTOS MEDIANTE EL MÉTODO FOTOELÁSTICO - Llosa D., M. (2005)
The residual tension and the molecular orientation in a material provide important information about its behavior. The presence or absence of residual tension determines the quality of the plastics used for the storage of information and others. In this work, a non destructive method was implemented for the evaluation of compact disks, as well as the storage of information in the same ones by means optic analysis of residual tension. A quantitative analysis of the tension state in different marks of CD was also made.